Both ascorbate peroxidase and glutathione peroxidase are active in removal of H2O2 from the cytosol of Hevea brasiliensis latex - Jacob, J. L. (2019)
Regular exploitation of rubber trees by tapping, a wounding process, leads to an increase in the production of reactive oxygen species. However, enzymes involved in the detoxification of these reactive oxygen species in latex are + still poorly characterised. This study showed that ascorbate peroxidase (APx, EC 1.11.1.11) and glutathione peroxidase (GPx, EC 1.11.1 9) activity were detected in the latex cytosol. Both activities were co-purified by onion exchange chromatography and could be partially separated by molecular gel filtration. APx was purified more than 300 times while GPx was purified 60 times, but further purification failed due to the lability of both enzymes. APx specific activity, which was insensitive to the + action of physiological effectors, was 10 times greater than that of specific GPx activity. The results showed that APx was a constitutive enzyme that played a major role in H2O2 removal in situ. The GPx specific activity was weak and limited by the + cytosolic-reduced glutathione content. However, GPx specific activity was regulated by several physiological effectors, including phosphate, and was enhanced by an increase in the frequency of ethylene treatment used to stimulate production of latex in rubber trees. Both APx and GPx, involved in the detoxification of reactive oxygen species in vivo, might play a role in stress resistance and/or regulate the duration of latex flow.